Thoracic radiculopathy as initial symptoms of hepatocellular carcinoma: A case report. Issue 30 (July 2018) - Kim, Yongmin; Kim, Sooa; Oh, Kiyoung; Kim, Yuntae
Abstract: Rationale: Among the patients who complain of neuralgia in the upper extremities, it is very rare to be caused by the first thoracic (T1) spinal nerve dermatome. Patient concerns: A 65-year-old presented with neuropathic pain of the left medial antebrachial cutaneous nerve and the medial brachial cutaneous nerve for 2 months. Diagnoses: Electrodiagnostic study revealed left thoracic radiculopathy mainly involving the T1 nerve root. Cervical spine magnetic resonance imaging revealed a metastatic tumor of T1 vertebral body compressing the left spinal cord and nerve root. After a systemic diagnostic work-up, he was finally diagnosed with primary hepatocellular carcinoma. Interventions: He received transarterial chemoembolization in the liver and radiotherapy to the T1 spine. Outcomes: After radiotherapy, the neuropathic pain was slightly improved. Lessons: If the patient is suspected of having thoracic radiculopathy, the physician should consider not only a herniated disc disease but also systemic disease. Because the prevalence of thoracic radiculopathy is very low and there is a high incidence of cancer that can spread to the spine in the elderly.